2007
DOI: 10.1080/14756360601143857
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition and protection of cholinesterases by methanol and ethanol

Abstract: The cholinesterases have been investigated in terms of the effects of methanol and ethanol on substrate and carbamate turnover, and on their phosphorylation. It was found: 1) that at low substrate concentrations the two alcohols inhibit all three tested cholinesterases and that the optimum activities are shifted towards higher substrate concentrations, but with a weak effect on horse butyrylcholinesterase; 2) that methanol slows down carbamoylation by eserine and does not influence decarbamoylation of vertebra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Uncertainty in the IC 50 value determination is caused by the type and concentration of the substrate used for measurements and therefore K i is a more reliable parameter, as it is a measure of enzyme ligand affinity in the absence of a substrate. The negative effect of the solvent mixture on the AChE enzyme activity when using ethanol or DMSO buffer should be tested, as ethanol or DMSO apparently increase the ligand inhibition potency due to AChE inhibition ( Fekonja et al, 2007 , Kumar and Darreh-Shori, 2017 ). Therefore, the effect of a solvent on AChE activity needs to be characterized and compensated properly.…”
Section: Introductionmentioning
confidence: 99%
“…Uncertainty in the IC 50 value determination is caused by the type and concentration of the substrate used for measurements and therefore K i is a more reliable parameter, as it is a measure of enzyme ligand affinity in the absence of a substrate. The negative effect of the solvent mixture on the AChE enzyme activity when using ethanol or DMSO buffer should be tested, as ethanol or DMSO apparently increase the ligand inhibition potency due to AChE inhibition ( Fekonja et al, 2007 , Kumar and Darreh-Shori, 2017 ). Therefore, the effect of a solvent on AChE activity needs to be characterized and compensated properly.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, two hydrolysis products were still found in the water system before 48 h, but HDC-G eventually disappeared at 48 h. Some studies have reported that methanol had an impairing effect on enzyme activities and that excessive use of methanol may even inactivate the enzyme. This could explain the difference in the conversion of NHDC between the methanol–buffer system and the deionized water–buffer system. , In deionized water, the glucosidase activity can be fully retained and therefore catalyze the hydrolysis of NHDC to produce HDC. However, in the methanol–buffer system, methanol partially inhibited the activity of glucosidase in whole-cell catalysts, thus preventing the complete synthesis of HDC.…”
Section: Resultsmentioning
confidence: 99%
“…This could explain the difference in the conversion of NHDC between the methanol−buffer system and the deionized water−buffer system. 31,32 In deionized water, the glucosidase activity can be fully retained and therefore catalyze the hydrolysis of NHDC to produce HDC. However, in the methanol−buffer system, methanol partially inhibited the activity of glucosidase in whole-cell catalysts, thus preventing the complete synthesis of HDC.…”
Section: Whole-cell Enzyme Cascade Hydrolysis Of Nhdcmentioning
confidence: 99%
“…The experiments in the presence of different reversible inhibitors were performed under the same conditions as the control experiments without them. Scheme and the corresponding equation (see the expression for A in the Appendix, and ref ) were used to describe the dependence of initial enzyme activity at different substrate concentrations (pS curves) in the absence and presence of inhibitors. Hydrolysis of o -nitrophenyl acetate in 25 mM phosphate buffer (pH 7) and 5% DMSO was monitored by the formation of o -nitrophenolate at 405 nm, with the Michaelis−Menten equation used for the analysis.…”
Section: Methodsmentioning
confidence: 99%